Creating awareness about traffic jam through engaged use of stop motion animation: boomerang - Wahid Zaman Raj, Md.; Tasnim Anika, Nishat; Sultana Anandi, Zakia; Sarker, Saurav; Kallol Ridoy, Udoy; Samaun Hasan, Md.; Shaikh Muhammad Allayear, Dr.; Salah Uddin, Dr. (International Journal of Engineering and Technology, 2019)
How can this stop motion animation be used to promote social awareness? In this paper, we examined the role of stop motion ani-mation on creating social awareness among people, focusing on traffic jam, wrote an overview overall process of making a stop mo-tion animation. In South Asian countries like ours, traffic jam is a hilarious problem. Because of traffic jam, we face a lot of incon-venience every single day. Actually, we are responsible for creating this problem. If we follow the laws and regulations of traffic, we can get rid of the problems caused by traffic jam. Because who knows! The problems we create today can be the problems that we will face tomorrow.Â